Manajemen Teaching Factory Konsentrasi Keahlian Perhotelan di SMK Negeri 1 Sukasada - Putu Savita Maharani; Made Riki Ponga Kusyanda; Ida Ayu Putu Hemy Ekayani (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2026)
This study aims to describe the management of the Teaching Factory in the Hospitality Expertise Concentration at SMK Negeri 1 Sukasada. The research focuses on four management functions—planning, organizing, actuating, and controlling—which are integrated into the Teaching Factory process, including product identification, competency scope analysis, production planning, resource adequacy analysis, product development, product delivery, and after-sales services. This study employs a descriptive qualitative approach with data collection techniques through observation, in-depth interviews with the principal, vice principals, teachers, and industry partners, as well as documentation.The results show that at the planning stage, the school has developed an industry-based learning plan integrated with the curriculum and involving the business, industrial, and professional world (DUDIKA). In the organizing stage, the Teaching Factory team structure was clearly established with task distribution according to areas of expertise. The implementation stage was carried out through a learning-by-doing model, allowing students to be directly involved in the production of hospitality goods and services with economic value. Meanwhile, the controlling stage was conducted continuously through internal evaluations and feedback from industry partners to ensure the quality of products and services. 1Corresponding author’s address: Universitas Pendidikan Ganesha e-mail: savita@undiksha.ac.id